La llengua al nord del País Valencià - Beltran Zaragozà, Andreu (Caplletra. Revista Internacional de Filologia, 1999)
A review of the various sub-dialect classifications of Catalan in the north of the Pais Valencià, together with a proposal distinguishing northern Valencian, with two subdialects, and southern Tortosí in the eastern border with Catalonia, provide an introduction to an elaborate summary of the main dialectal research on the area. This is followed by the features characterizing these subdialects and a description of the area involved. There are seven phonetic phenomena: an unpalatalized production of /tS/, the survival and loss of intervocalic /d/, the opening of initial /e/, the disappearance and survival or/r/and some plosives at the end of words; in addition, the paper contains six sections on morphology, noun flexion, the masculine definite article, the degrees of demostratives and locatives, the allomorphic varieties of first and third person of indicative present, subjunctive present and subjunctive imperfect in first conjugation verbs. The paper ends with some comments on lexis, whose footnotes include the situation of the same features by the 18th century, according to the documents of the time.